Hekhalot literature in translation : major texts of Merkavah mysticism - Davila, James R., 1960- (Supplements to The Journal of Jewish Thought and Philosophy, 2013)
The Hekhalot literature is a motley collection of textually fluid and often textually corrupt documents in Hebrew and Aramaic which deal with mystical themes pertaining especially to God's throne-chariot (the Merkavah). They were composed between late antiquity and the early Middle Ages, with roots in earlier traditions and a long and complex subsequent history of transmission. This volume presents English translations of eclectic critical texts, with a full apparatus of variants, of most of the major Hekhalot documents: Hekhalot Rabbati ; Sar Torah ; Hekhalot Zutarti ; Ma'aseh Merkavah ; Merkavah Rabba ; briefer macroforms: The Chapter of R. Nehuniah ben HaQanah , The Great Seal-Fearsome Crown , Sar Panim , The Ascent of Elijah ben Avuyah , and The Youth ; and the Hekhalot fragments from the Cairo Geniza.